Innovation for Sustainable Development - Review of Uzbekistan - United Nations Economic Commission for Europe (United Nations, 2022)
The Innovation for Sustainable Development Review of Uzbekistan contains the outcomes of a policy advisory exercise that drew on the experience accumulated by the UNECE in the identification of good practices and policy lessons in the area of knowledge-based development, with particular reference to the problems of countries with economies in transition. It provides a set of recommendations and policy options to stimulate innovation activity in the country, enhance its innovation capacity and improve the overall efficiency of the national innovation system.